The Nuclear Translocation of Heme Oxygenase-1 in Human Diseases - Yang, Qing; Wang, Wenqian (Frontiers in Cell and Developmental Biology, 2022)
Heme oxygenase-1 (HO-1) is a rate-limiting enzyme in the degradation of heme to generate carbon monoxide (CO), free iron and biliverdin, which could then be converted to bilirubin by biliverdin reductase. HO-1 exhibits cytoprotective effects of anti-apoptosis, anti-oxidation, and anti-inflammation via these byproducts generated during the above process. In the last few years, despite the canonical function of HO-1 and possible biological significance of its byproducts, a noncanonical function, through which HO-1 exhibits functions in diseases independent of its enzyme activity, also has been reported. In this review, the noncanonical functions of HO-1 and its translocation in other subcellular compartments are summarized. More importantly, we emphasize the critical role of HO-1 nuclear translocation in human diseases. Intriguingly, this translocation was linked to tumorigenesis and tumor progression in lung, prostate, head and neck squamous cell carcinomas and chronic myeloid leukemia. Given the importance of HO-1 nuclear translocation in human diseases, nuclear HO-1 as a novel target might be attractive for the prevention and treatment of human diseases.